ADAPTASI CERITA RAKYAT DALAM DRAMA TARI CUPAK GURANTANG SEBAGAI PRODUK SENI WISATA DI DESA SEMBALUN BUMBUNG - Khairul Azmi; Aswan Kailani M.sn; Very Adrian; Nil Wahyuni; Zarina; Mia Audina (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study aims to analyze the process of adapting the Cupak Gurantang folktale into a dance-drama performance designed as a tourism art product in Sembalun Bumbung Village, East Lombok. As an oral literary heritage rich in moral values, Cupak Gurantang holds significant potential for development beyond its conventional educational function. The study employs a qualitative method utilizing ethnochoreological and performing arts management approaches. Data were gathered through field observations, in-depth interviews with traditional leaders, and a review of documents regarding the original story structure. The findings indicate that the adaptation process involved reconstructing the narrative arc, stylizing dance movements, and adjusting the performance duration to align with the characteristics and interests of tourists. The Cupak Gurantang dance-drama presented in Sembalun Bumbung serves as a strategy for local cultural preservation rooted in community economic empowerment through the tourism sector. The study concludes that transforming the folktale into a tourism-oriented performance strengthens the identity of Sembalun Bumbung as a tourist destination. These findings indicate that cultural adaptation does not always lead to commercialization that erodes authenticity, but can instead be a mechanism for preserving cultural heritage while increasing the competitiveness of tourist destinations through the active participation of local communities.